Startup Experience Trip in Strengthening Social Capital and Empowering the Economy of Partner Village - Ronald Tri Pamungkas; Ravik Karsidi; Rahesli Humsona (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
This study investigates the role of the startup Experience Trip in enhancing social capital and empowering partner village communities in Klaten Regency. Employing a qualitative case study methodology, the research analyses Experience Trip's function as a bridge among stakeholders involved in the development of community-based tourism (CBT). The findings indicate that Experience Trip not only provides alternative tourism packages including empowering, live-in, and travel options but also serves as a facilitator of community empowerment through training and mentorship programs for village communities. Utilising Robert D. Putnam’s social capital framework, encompassing networks, norms, and trust, this study reveals that Experience Trip has effectively cultivated bridging social capital among different groups, fostered experience-oriented tourism, and established trust through a community involvement approach that tends to be top-down, facing challenges related to lower community participation. The implications of this study underscore the importance of inclusive collaboration and the integration of sustainability principles into tourism startup business models to reinforce long-term socio-economic benefits.